ANALYSIS OF OIL PALM FARMING RESULTS ON COMMUNITY WELFARE IN HURISTAK DISTRICT PADANG LAWAS DISTRICT - Harahap, Misna Doharni; Syafina Rambe, Dhea Nita; Ruslan, Dede; Sari, Raina Linda (Inovbiz: Jurnal Inovasi Bisnis, 2024)
The plantation sector, which includes coffee, pepper, rubber and palm oil, has quite good prospects for the lives of farmers. One of the plantation commodities that has relatively high value and can support the Indonesian economy is palm oil. Palm oil is a plantation commodity important for income and employment and a source of foreign exchange because palm oil has high economic value. However, the many job opportunities provided by the agricultural sector are a challenge among the community due to the low level of education and knowledge about technology, which is still taboo, causing people in Huristak District to become agricultural laborers on oil palm farming land with a low level of productivity. This research aims to determine the factors of experience, education, skills, income, palm oil prices, production, labor and productivity relevant to improving community welfare in Huristak District, Padang Lawas Regency. Data processing uses Confirmatory factor analysis (CFA) and Multiple Linear Regression. The results of the Confirmatory Factor Analysis (CFA) test in the KMO and Bartlett's test tables show that the factors of palm oil price, experience, income and skills significantly affect the community's welfare in Huristak District.In contrast, education, production, labor and productivity have a negative or insignificant effect on welfare. The people of Huristak District. The results of multiple linear regression testing show that simultaneous hypothesis testing of palm oil prices, experience, income and skills together have a positive and significant effect on the welfare of the people of Huristak District.Keywords: Â Prices, Experience, Income, Skills and Welfare.